Application of Critical Theory in Nursing Research Design: Systematic Review - Dwi Retnaningsih; Muhammad Ridlo; Bagas Biyanzah Drajad Pamukhti; Eko Budi Laksono; Megah Andriany (Alta Dharma Publisher, 2020)
A person infected with HIV/ AIDS has many things to deal with in their daily lives. Changes that occur within and outside of people living with HIV AIDS (PLWHA) create negative perceptions about themselves and affect their self-development. Nursing research on illness perception has been proven to be related to the outcome of one's treatment. This study used the concept of philosophical theory in nursing research. The critical theory ontologically was similar to post-positivism, which critically assesses objects or reality (critical realism) unnoticeable correctly by human observation. Epistemologically, critical theory was an inseparable relationship between the observer and reality. Therefore, this theory emphasizes the concept of subjectivity in finding a science. This theory perceives reality as an integral variable from the research subject. The values ??of the subject influence the truth of reality. Axiology was a study of the benefits ??on the purpose of the knowledge utilization that refers to the development and selection of the research field priorities and the implementation of knowledge utilization. People living with HIV / AIDS (PLWHA) are perceived negatively by both family and community. This negative judgment leads to the negative perception of PLWHA, which impacts on the inadequate treatment and worse condition of the patients. The negative perception of PLWHA towards their illness can be measured using qualitative methods with the focus group discussion (FGD) method or in-depth interview. PLWHA with a poor perception of the disease can change their perspective to be more positive and can be cooperative in conducting treatment by using therapeutic communication techniques in a professional manner